Efficacy of blunt abdominal trauma scoring system in management of blunt abdominal trauma - Shah, D. K.; Patel, Krupal M.; Patel, Shreyansh; Padshala, Renish; Doliya, Tejas (International Surgery Journal, 2022)
Background: Although there are many scores to evaluate a patient having trauma, BATSS is a newer score specifically designed for blunt abdominal trauma which is not adequately studied. The objective was to study the efficacy of BATSS by comparing it with conventional experience-based management of Blunt abdominal trauma. Methods: 100 patients presenting with blunt abdominal trauma between March 2019 to May 2020 were randomly selected. Patients were treated by conventional experience-based management and it was compared with management guided by BATSS by prospective observation. Analysis was done by assessing need for CT scan of abdomen and laparotomy to check efficacy of BATSS. Results:100 patients were included in study. CT Abdomen is rarely required in low-risk category (BATSS<8, p <0.0001). In Moderate and High-risk category (BATSS>8), CT Abdomen is required to accurately identify Intra-abdominal injury (p=0.0006 and 0.0965 respectively). Laparotomy may be necessary in any risk category patient for hollow viscous perforation. BATSS does not have a variable like X-ray-Chest standing to diagnose hollow viscous perforation. So, some patients in Low-risk category may also need Laparotomy (p 0.06892) which is not indicated by BATSS. Not all patients in high-risk category needs laparotomy (p=0.00009). Conclusions: Variables used to score the severity of trauma are inadequate and some patients would be improperly categorised in blunt abdominal trauma scoring system. So, we conclude that BATSS is not useful in our setup and requires modifications.